Targeting malaria in high-risk populations in low endemic regions in northern Namibia: a quasi-experimental controlled trial to reduce malaria in seasonal agricultural workers and cattle herders - Roly Gosling; Adam Bennett; Petrina Uusiku; Henry Ntuku; Bryan Greenhouse; Jennifer L Smith; Jerry O Jacobson; Cara Smith-Gueye; Francois Rerolle; Ashley Morgan Burke; Tabeth Mwema; Keirstinne Turcios; et al. (BMJ Global Health, 2025)
Background Agricultural worksites are rarely targeted by malaria control programmes, yet may play a role in maintaining local transmission due to workers’ high mobility, low intervention coverage and occupational exposures.Methods A quasi-experimental controlled intervention study was carried out in farming and cattle herding populations in northern Namibia to evaluate the impact of a targeted malaria intervention package. Eight health facility catchment areas in Zambezi and Ohangwena Regions were randomised to an intervention arm and eligible individuals within worksites in intervention areas received targeted drug administration with artemether-lumefantrine, mop-up indoor residual spraying and long-lasting insecticidal nets, combined with distribution of topical repellent in Zambezi Region. Impact on malaria outcomes and intervention coverage was evaluated over a single transmission season using pre-intervention and post-intervention cross-sectional surveys in a random subset of worksites and community incidence from passively detected cases. Entomological collections and residual efficacy assays on canvas and tarpaulin were conducted.Results Delivery of a single intervention round was associated with a reduction in the prevalence of malaria (OR 0.24, 95% CI 0.1 to 0.5; risk difference (RD) −6.0%, 95% CI −9.4 to –2.8). Coverage of at least one intervention increased (RD 51.6%, 95% CI 44.4 to 58.2) among the target population in intervention compared with control areas. This effect was largely driven by results in Zambezi Region, which also observed a decline in community incidence (−1.29 cases/1000 person-weeks, 95% CI −2.2 to –0.3). Residual efficacy of pirimiphos-methyl (Actellic) on tarpaulin and canvas was high at 24hours but declined to 44.6% at 4 months.Conclusion The study shows that targeted delivery of malaria interventions to cattle herders and agricultural workers at worksites has potential to impact local transmission. Findings highlight the need for further research on the role of key populations in Plasmodium falciparum transmission in Namibia.Trial registration number NCT04094727.